Penerapan Aturan Asosiasi Algoritma Apriori Terhadap Penjualan Thai Tea Pada PT Nyonya Besar Lestari - Normah Normah; Cristine Olivia (LPPM Universitas Bina Sarana Informatika, 2020)
Competition in the business world, especially in the increasingly lively beverage sales, requires the sellers to find strategies to increase sales. More and more sales data every day can be used to develop marketing strategies if processed correctly. To find out the most sales Apriori Algorithm is needed to be able to find out and with the help of Rapidminer tools, products with the most sales can be known. Apriori algorithm including the type of association that has raised the attention of many researchers to produce an efficient algorithm is the analysis of high frecuency patterns (frequent pattern mining) in this study can be implemented on the interest of buying drinks with the data used are 31 transactions with a minimum support or 30% and minimum confidence 60%.